Determinants of Capital Structure: The Case of Chinese Listed Companies - Li, Ying (2006)
Capital structure is the proportion of all kinds of funds utilized by enterprises, which has influence not only on the cost of capital and market value of enterprises but also corporate governance and the stability of the economy. Therefore, the theory of capital structure requires special attention. Many researchers have discussed the determinants of optimal capital structure. In China, capital structure is more complicated due to the imperfections of the market and the failure of the investor protection. This dissertation analyses the determinants of the capital structure of the listed companies in china. And how powerful classic capital structure theory is on explaining the finance behavior of the listed companies in china. This current study specially explores capital structure in Chinese listed company. The paper assesses different theories about capital structure, and applies these theories on the research of Chinese capital structure. The paper used JuLing Database, which contains market and accounting data of more than 1000 Chinese listed companies from Year 1996 to 2004, to document the characteristics of these firms in terms of capital structure. From this paper, we find that the empirical result of micro influential factors for capital structure in China corresponds to modern corporation capital structure theory of western countries. We also find that, profitability is endogenous for the capital structure analysis of Chinese listed companies, and the different measurement to explanatory variables will affect empirical results. Two regression models are used in this paper, to analysis the capital structure of listed company. The 2SLS model rather than OLS model seems better in explaining the features of Chinese listed company.